Aberrantly expressed CEACAM6 is involved in the signaling leading to apoptosis of acute lymphoblastic leukemia cells - Kanderová, Veronika; Hrusák, Ondrej; Kalina, Tomás (Experimental hematology, 2010)
OBJECTIVE: The aberrant expression of myeloid antigens on acute lymphoblastic leukemia (ALL) cells is a well-documented phenomenon. So far, there have been no reports of a functional consequence of this aberrant expression. The granulocytic marker carcinoembryonic antigen-related cell adhesion molecule 6 (CEACAM6, CD66c) is a GPI-anchored molecule that is reported to be the most frequently aberrantly expressed myeloid marker in ALL with a strong correlation with genotype. MATERIALS AND METHODS: We mimicked CEACAM6 signaling in ALL cells by cross-linking with anti-CEACAM6 antibody. Next, we measured a response to CEACAM6 signaling by integrin subunits expression, integrin ligand binding, phosphorylation of extracellular signal-regulated kinase 1/2 (Erk1/2), Akt, and p38 mitogen-activated protein kinase (MAPK) and apoptosis by flow cytometry. RESULTS: Following CEACAM6 cross-linking in ALL cells, we detected Erk1/2, Akt, and p38 MAPK phosphorylation and integrin upregulation, as well as enhanced binding of integrin ligands (vascular cell adhesion molecule-1 [VCAM-1] and intercellular cell adhesion molecule-1 [ICAM-1]). However, CEACAM6 signaling resulted in an increase in apoptosis, unlike other GPI-anchored molecules, such as CD24. CONCLUSION: The present study is the first to demonstrate the functional consequences of CEACAM6 cross-linking in B-cell precursor ALL cells.
Keywords: MAP Kinase Signaling System; p38 Mitogen-Activated Protein Kinases; apoptóza; Intercellular Adhesion Molecule-1; Cell Line, Tumor; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; molekuly buněčné adheze; Integrins; integriny; CD antigeny; Antigens, Neoplasm; Apoptosis; mitogenem aktivovaná proteinkinasa 3; GPI-vázané proteiny; lidé; Immunologic Capping; onkogenní protein v-akt; protilátky nádorové; imunologický capping; mitogenem aktivované proteinkinasy p38; regulace genové exprese u leukemie; Phosphorylation; Antigens, CD; fosforylace; GPI-Linked Proteins; mezibuněčná adhezivní molekula-1; Cell Adhesion Molecules; Mitogen-Activated Protein Kinase 3; Antibodies, Neoplasm; Gene Expression Regulation, Leukemic; pre-B-buněčná leukemie; Oncogene Protein v-akt; antigeny nádorové; MAP kinasový signální systém; nádorové buněčné linie; Humans